Reflexões sobre as incidências tributárias no Brasil e suas relações com o desenvolvimento socioeconômico nacional - Luciano Henrique Fialho Botelho; Luíz Antônio Abrantes (Ciências Sociais Unisinos)
This essay, based on theories of public finances and the optimal taxation model, sought to reflect on the national tax landscape. Its great motivation was due to the existence of very few studies that deal systematically with the analysis of the various forms of tax incidence and the need for greater attention by the government and society in relation to the National Tax System (STN). The analysis of the current legislation with comparative effect in several published works on the subject was promoted. The placements resulting from the effort of this trial demonstrate that the STN cannot appropriate any of the ideals of the optimal taxation, neutrality, simplicity, progressivity, and fairness model. Finally, some suggestions of the literature for a tax reform in Brazil were discussed and the choice of a system with a high tax burden was highlighted, in the face of the search for a welfare state.